2023
DOI: 10.3390/ijms24043393
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, Iodine and Iron–Essential Trace Elements for Thyroid Hormone Synthesis and Metabolism

Abstract: The adequate availability and metabolism of three essential trace elements, iodine, selenium and iron, provide the basic requirements for the function and action of the thyroid hormone system in humans, vertebrate animals and their evolutionary precursors. Selenocysteine-containing proteins convey both cellular protection along with H2O2-dependent biosynthesis and the deiodinase-mediated (in-)activation of thyroid hormones, which is critical for their receptor-mediated mechanism of cellular action. Disbalances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 123 publications
1
18
0
1
Order By: Relevance
“…At the meantime, more and more studies are focusing on the role of trace elements in the development of diabetes. Although trace elements are found at extremely low levels in the body, they are involved in the composition of molecular structures such as hormones, nucleic acids and catalytic enzymes 31 . Trace elements are closely related to the biological functions of molecules, and the abnormal levels can affect the metabolism and functions of tissues and cells 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the meantime, more and more studies are focusing on the role of trace elements in the development of diabetes. Although trace elements are found at extremely low levels in the body, they are involved in the composition of molecular structures such as hormones, nucleic acids and catalytic enzymes 31 . Trace elements are closely related to the biological functions of molecules, and the abnormal levels can affect the metabolism and functions of tissues and cells 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Although trace elements are found at extremely low levels in the body, they are involved in the composition of molecular structures such as hormones, nucleic acids and catalytic enzymes. 31 Trace elements are closely related to the biological functions of molecules, and the abnormal levels can affect the metabolism and functions of tissues and cells. 32,33 For example, in a meta-analysis of 22 cohort studies, Zhao et al identified an inverse association between magnesium intake and diabetes.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…Compared with simple Se deficiency, concurrent Se and iodine deficiency further diminishes the activity of glutathione peroxidase, increasing the vulnerability of target cells, such as chondrocytes, to oxidative stress and leading to chondrocyte apoptosis ( 114 ). Moreover, Se supplementation may expedite iodine metabolism in instances of insufficient iodine intake ( 113 ). This leads to the deiodination of circulating thyroid hormones, accelerating iodine loss in the kidney and faeces and exacerbating iodine deficiency ( 113 ).…”
Section: Mechanism Underlying the Interaction Between Se And Iodine I...mentioning
confidence: 99%
“…Moreover, Se supplementation may expedite iodine metabolism in instances of insufficient iodine intake ( 113 ). This leads to the deiodination of circulating thyroid hormones, accelerating iodine loss in the kidney and faeces and exacerbating iodine deficiency ( 113 ). The administration of Se supplements, whether preventive or interventional, should be preceded by ensuring adequate iodine levels to prevent iodine loss.…”
Section: Mechanism Underlying the Interaction Between Se And Iodine I...mentioning
confidence: 99%
“…The trace element selenium (Se) is an essential micronutrient that is incorporated in the form of the amino acid selenocysteine (Syc) in selenoproteome, consisting of 25 proteins (selenoproteins) most of which are in the thyroid, the latter being iodothyronine deiodinase (DIO1), glutathione peroxidases (GPXs), thioredoxin reductases (TXRNDs), and selenoprotein P (SELENOP) [9]. SELENOP, which plays an important role in Se storage, transport, and supply, is found abundantly in the thyroid, and represents a reliable biomarker for Se status in humans [10].…”
Section: Seleniummentioning
confidence: 99%